Can anxiety-like behavior and spatial memory predict the extremes of skilled walking performance in mice? An exploratory, preliminary study - Schiavo, Aniuska; Martins, Lucas Athaydes; Wearick-Silva, Luís Eduardo; Orso, Rodrigo; Xavier, Léder Leal; Mestriner, Régis Gemerasca (Frontiers in Behavioral Neuroscience, 2023)
Skilled walking is influenced by memory, stress, and anxiety. While this is evident in cases of neurological disorders, memory and anxiety traits may predict skilled walking performance even in normal functioning. Here, we address whether spatial memory and anxiety-like behavior can predict skilled walking performance in mice. A cohort of 60 adult mice underwent a behavioral assessment including general exploration (Open Field), anxiety-like behavior (Elevated Plus Maze), working and spatial memory (Y-Maze and Barnes Maze) and skilled walking performance (Ladder Walking Test). Three groups were established based on their skilled walking performance: superior (SP, percentiles ≥ 75), regular (RP, percentiles 74 to 26) and inferior (IP, percentiles ≤ 25) performers. Animals from the SP and IP groups spent more time in the elevated plus maze closed arms compared to the RP group. With every second spent in the elevated plus maze closed arms, the probability of the animal exhibiting extreme percentiles in the ladder walking test increased by 1.4%. Moreover, animals that spent 219 seconds (73% of the total time of the test) or more in those arms were 4.67 times more likely to exhibit either higher or lower percentiles of skilled walking performance. We conclude anxiety traits could influence skilled walking performance in facility-reared mice.